Slurry Seal: Teknologi Pada Preservasi Perkerasan Lentur - Tisara Sita (Journal of Airport Engineering Technology (JAET), 2021)
Cracks in the flexible pavement is a condition that occurs due to non-uniform stress distribution of loads on the pavement, resulting in damage to the weaker material, which then develops to other parts. Several types of treatment toovercome the cracks are:Crack Treatment; Surface Treatment; Crack Repair,andPavement Rehabilitation. One type of treatment in the preservation of flexible pavement cracking isslurry seals. Slurry sealis a stable mixture of slow, steady emulsion asphalt, fine aggregate with continuous gradation, filler and water. The advantages ofthe slurry seal areefficient, durable, and applicable. Applicationslurry seal inthe preservation of flexible pavement canimprove the life of the pavement for up to 8 years. In addition, manytreatment of type slurrysealreducing various thedamageof pavement.